Konflik Batin Tokoh Utama Dalam Drama Romeo and Juliet dan Drama Atas Nama Cinta - Fitria Amalia; Ramadhan Ramadhan (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
This study aims to analyze two literary works and to present the results of the analyzes that the author has reviewed as a consideration or reference for comparative literary studies with the title "The inner conflict of the main character in the drama Romeo and Juliet by William Shakespeare and Atas Nama Cinta by Agus R. Sardjono. "Shows the inner conflict of the story of Romeo and Juliet about love wrapped in a grudge between the two families, which causes the murder and suicide of the main character until the family finally reconciles. As well as the comparison with In the Name of Love, which is a love drama wrapped in comedy that has a deep meaning about love and power and is closely related to the drama Romeo and Juliet because they have similar inner conflicts.This study uses a Literary Psychology approach with Sigmund Freud's theory. The method used in this research is descriptive qualitative. The sources of this research are two drama scripts, namely Romeo and Juliet by William Shakespeare and Atas Nama Cinta by Agus R. Sardjono. From the analysis of the two drama scripts, it can be rejected. The conflict in the two drama scripts Romeo and Juliet by William Shakespeare and Atas Nama Cinta by Agus R. Sarjono experienced an inner conflict with the main character. According to Sigmund Freud's theory, there is an ego in the event of this request. Ego is a psychological responsibility and arises because of the organism's need for good relations (reality).